Los pantalones del osito - Hissey, Jane. (Barcelona : Editorial Zendrera Zariquiey, 1998)
While looking for his missing trousers, Osito discovers that the other toys have found many different uses for them.
Keywords: Teddy bears -- Juvenile fiction; Pants -- Juvenile fiction; Toys -- Juvenile fiction